THE CORRELATION BETWEEN STUDENTSâ€™ MOTIVATION AND VOCABULARY MASTERY - Rohepta, Anggun (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2020)
The aims of this research to find out the significant correlation between studentsâ€™ motivationmand vocabulary mastery at the tenth gradeystudents of SMA N 1 Tangen Kabupaten Sragen in the 2019/2020 academic year.IThe researcher conducted a correlation research. Tomcollect the data the researcher held try-out and test. After collecting the data,jthe researcher analyzed the data using validity and reliability test.jThe calculating of the collected data showsmthat the coefficient of the correlation between studentsâ€™omotivation (X) and vocabularybmastery (Y) was 0,130 with the level significant 5% for degreemof freedom (df) = 26 was 0,388 and the level significant 1% for degree of freedom (df) =26 was 0,496 which Ho = rxy < rtable, it means r observation (rxy) was lowest than rtable and it was concluded that the Null Hypothesis was accepted, there was a negative of significant correlation between studentsâ€™ motivation (X) and vocabulary mastery(Y) was rejected. Therefore, the alternative hypothesis was rejected. It can bemconcluded that there is negativemcorrelation between studentsâ€™wmotivation and vocabulary mastery at the tenth grade students of SMA N 1 Tangen Kabupaten Sragen in the 2019/2020 academic year.â€Keyword: CorrelationmStudy, Studentsâ€™mMotivation. VocabularymMastery. Quantitative.